Bacteriological profile of critically ill patients with chronic obstructive pulmonary disease in respiratory intensive care unit in Assuit University Hospital - Maha K. Ghanem (The Egyptian Journal of Bronchology, 2019)
Abstract Background Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is responsible for a high proportion of morbidity and antibiotic use. This study aimed to identify the causative bacteria, antimicrobial sensitivity, and resistance of hospitalized patients in respiratory ICU owing to AECOPD. Patients and methods This prospective study was performed at Assiut University Hospitals on 50 patients with AECOPD who needed ICU admission. Samples included sputum for staining and culture. Samples were cultured on two bacteriological media (blood and MacConkey’s agars) to detect gram-positive and gram-negative organisms and their sensitivity to different antibiotics. Results Klebsiella pneumoniae was the most frequently detected organism in 29 (58%) patients followed by Pseudomonas aeruginosa in 14 (28%) patients, methicillin resistant Staphylococcus aureus (MRSA) in eight (16%) patients, Acinetobacter baumannii in seven (14%) patients, Proteus spp. and Staphylococcus aureus in five (10%) patients each, and Escherichia coli in three (6%) patients. No growth was reported in three (6%) patients. Among gram-positive organisms, linezolid had the upper hand of efficacy followed by vancomycin and teicoplanin. Gram-negative organisms had high rate or resistance to most tested antibiotics. Frequency of death was more (62.5%) in patients with MRSA. Conclusion K. pneumoniae was the most frequent organism followed by P. aeruginosa, MRSA, and A. baumannii. The isolated bacterial strains were characterized by high resistance rates to the most used antimicrobials. Mortality rate was more among patients with MRSA.